Uji Klirens dan Uji Pirogenitas sebagai Bagian dari Penentuan Mutu Biologi Sediaan 90Y-EDTMP - Sulaiman, Sulaiman; Aguswarini, Sri; Karyadi, Karyadi; Chairuman, Chairuman; Setiawan, Gatot; HG, Adang; Subur, M. (Jurnal Kefarmasian Indonesia, 2018)
Cancer is one of the causes of death in Indonesia and even the world. Nuclear medicine techniques with radiopharmaceuticals and SPECT are one of the ways to treat cancer, but their use in Indonesia is not yet popular. Radiopharmaceuticals marked with radionuclide emitting beta (β) radiation are proven to be used for cancer therapy, one that has been developed in PTRR-BATAN is 90Y-EDTMP. Yttrium-90 is used in nuclear medicine by utilizing β radiation (E max 2.28 MeV). The β energy which is produced from the decay process of 90Y radionuclides to 90Zr can kill cancer cells. This study aimed to provide information about the substances biological effects so that preventive measures can be taken to protect humans. This study conducted evaluation of the 90Y-marked radiopharmaceutical (90Y produced from a 90Sr / 90Y generator which is 90Y-EDTMP) encompasses clearance test, pyrogen test, and dose safety test in experimental animals. The clearance test utilized mice, the pyrogen test utilized rabbits, and the dose safety test utilized mice. The results of the clearance test showed that 90Y-EDTMP compound which was excreted in 192 hour was 49.70% through urine and 14.59% through feces. The total excretion of 90Y-EDTMP within 192 hours was 64.57%. Based on the results of clearance tests with calculations, 90Y of 90Sr / 90Y generators in 90Y-EDTMP dosage form had 84.2 hours of half-life, 36.5 hours of an effective half-life and 52.7 hours of a residence time. Pyrogen test results showed pyrogen-free. The 90Y-EDTMP dose safety test showed that the dose is safe and not deadly. The development of 90Y-EDTMP is expected to be improved to produce radiopharmaceuticals for cancer therapy in order to make a real contribution in public health services.